Incidental Findings on Cone Beam Computed Tomography Studies outside of the Maxillofacial Skeleton - Sevin Barghan; Mehrnaz Tahmasbi Arashlow; Madhu K. Nair (Hindawi Limited, 2016)
Objective. To define the presence and prevalence of incidental findings in and around the base of skull from large field-of-view CBCT of the maxillofacial region and to determine their clinical importance. Methods. Four hundred consecutive large fields of view CBCT scans viewed from January 1, 2007, to January 1, 2014, were retrospectively evaluated for incidental findings of the cervical vertebrae and surrounding structures. Findings were categorized into cervical vertebrae, intracranial, soft tissue, airway, carotid artery, lymph node, and skull base findings. Results. A total of 653 incidental findings were identified in 309 of the 400 CBCT scans. The most prevalent incidental findings were soft tissue calcifications (29.71%), followed by intracranial calcifications (27.11%), cervical vertebrae (20.06%), airway (11.49%), external carotid artery calcification (10.41%), lymph node calcification (0.77%), subcutaneous tissue calcification and calcified tendonitis of the longus colli muscle (0.3%), and skull base finding (0.15%). A significant portion of the incidental findings (31.24%) required referral, 17.76% required monitoring, and 51% did not require either. Conclusion. A comprehensive review of the CBCT images beyond the region of interest, especially incidental findings in the base of skull, cervical vertebrae, pharyngeal airway, and soft tissue, is necessary to avoid overlooking clinically significant lesions.